Strengthening clinical cancer research in the United Kingdom. - Stead, M; Cameron, D; Lester, N; Parmar, M; Haward, R; Kaplan, R; Maughan, T; Wilson, R; Campbell, H; Hamilton, R; Stewart, D; O'Toole, L; et al. (2011)
BACKGROUND: In 1999, 270,000 cases of cancer were registered in the United Kingdom, placing a large burden on the NHS. Cancer outcome data in 1999 suggested that UK survival rates were poorer than most other European countries. In the same year, a Department of Health review noted that clinical trials accrual was poor (<3.5% of incident cases) and hypothesised that increasing research activity might improve outcomes and reduce the variability of outcomes across England. Thus, the National Cancer Research Network (NCRN) was established to increase participation in cancer clinical research. METHODS: The NCRN was established in 2001 to provide a robust infrastructure for cancer clinical research and improvements in patient care. Remit of NCRN is to coordinate, support and deliver cancer clinical research through the provision of research support staff across England. The NCRN works closely with similar networks in Scotland, Wales and the Northern Ireland. A key aim of NCRN is to improve the speed of research and this was also assessed by comparing the speed of study delivery of a subset of cancer studies opening before and after NCRN was established. RESULTS: Patient recruitment increased through NCRN, with almost 32,000 (12% of annual incident cases) cancer patients being recruited each year. Study delivery has improved, with more studies meeting the recruitment target - 74% compared with 39% before NCRN was established. CONCLUSION: The coordinated approach to cancer clinical research has demonstrated increased accrual, wide participation and successful trial delivery, which should lead to improved outcomes and care.